Design of Sprocket and Chain Transmission System on Seaweed Dryer Machine - Prihanto, Prihanto; Murdianto, Deny; Nurdin, Muhammad Firdan (Universitas Borneo Tarakan, 2024)
Seaweed is an abundant aquatic product in Indonesia, where around 80% of its production is sold dry. The drying process of seaweed is done in 2 ways, namely direct sunlight or a drying machine method. Seaweed drying machines require a power transmission system to optimize the drying process. The aim of this study is to design a transmission system for a ratary dryer drying machine. The method used in this study is the design and selection of a sprocket and chain transmission system. The research result showed that the chain used was number 25, a single chain with 59 links and a ratio of 15 sprocket pins to 38. The axle distance is 100.4 mm using steel shaft material bearing with the symbol S30C with the drip lubrication method. The sprocket and chain that have been designed were capable of transmitting 14 watts of electric dynamo energy with a torque of around 4.75 Nm at 19.56 revolutions for a load of 1 kg of seaweed.